1994
DOI: 10.1111/j.1398-9995.1994.tb00794.x
|View full text |Cite
|
Sign up to set email alerts
|

Local side‐effects during 4‐year treatment with inhaled corticosteroids – a com between pressurized metered‐dose in and Turbuhaler®

Abstract: Local side-effects, such as hoarseness and oropharyngeal candidiasis, are often seen during treatment of patients with inhaled corticosteroids (ICS). We investigated whether changing from pressurized metered-dose inhalers (pMDI) to Turbuhaler influenced the type and frequency of local side-effects. Local side-effects were recorded for a 2-year period in which 154 patients used ICS pMDI with a spacer device. They were followed for an equally long period of time (26.2 +/- 5.7 months) while using Turbuhaler, as w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
35
1
1

Year Published

1994
1994
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(40 citation statements)
references
References 9 publications
3
35
1
1
Order By: Relevance
“…Holding chambers and spacers are used to decrease the oropharyngeal deposition from a P-MDI, in order to avoid local side-effects such as hoarseness and oropharyngeal candidiasis. In a recent study in 154 patients using a steroid P-MDI with spacer, the frequency of local side-effects, mainly hoarseness, was reduced from 21 to 6% when transferring from P-MDI to budesonide via Turbuhaler® [12].…”
Section: Discussionmentioning
confidence: 98%
“…Holding chambers and spacers are used to decrease the oropharyngeal deposition from a P-MDI, in order to avoid local side-effects such as hoarseness and oropharyngeal candidiasis. In a recent study in 154 patients using a steroid P-MDI with spacer, the frequency of local side-effects, mainly hoarseness, was reduced from 21 to 6% when transferring from P-MDI to budesonide via Turbuhaler® [12].…”
Section: Discussionmentioning
confidence: 98%
“…In the last meeting in our study, the oral evaluation score average of the study group was found to be better than the control group. In a study by Selroos et al (24), which examined the local side effects of inhaler corticosteroids during 4 years of treatment by comparing metered dose inhalers and turbuhaler devices, patients using both devices were told to rinse their mouths with water after inhalation. It was reported that the incidence of local side effects such as candidiasis or hoarseness of voice in patients using a metered dose inhaler reduced from 21% to 6% and there were no side effects in patients using a turbuhaler.…”
Section: Discussionmentioning
confidence: 99%
“…Развитие дисфонии зависит от дозы иГКС и чаще встречается у лиц с повышен-ной голосовой нагрузкой. В некоторых исследовани-ях показано, что при приеме иГКС с помощью ДПИ снижается частота развития дисфонии, что, возмож-но, обусловлено разной позицией голосовых связок при использовании ДПИ и ДАИ [11]. Лечение дис-фонии заключается в соблюдении голосового режи-ма, сокращении дозы иГКС до минимально необхо-димой для контроля над БА, использовании ДПИ или применении иГКС, являющихся пролекарством (БДП, циклесонид).…”
Section: нежелательные эффекты игксunclassified